Pengaruh Kepemimpinan Kepala Madrasah, Motivasi Kerja dan Budaya Kerja terhadap Kinerja Guru Madrasah Ibtidaiyah di Kecamatan Sawang Kabupaten Aceh Utara - Suheri, Edi; Syaripuddin, Syaripuddin; Purnamasari (Singkite Journal, 2024)
The aim of this research is to determine: a) the relationship between head leadership, work motivation and work culture. b) partial influence of madrasa head leadership, work motivation and work culture on teacher performance, b) Simultaneous influence of madrasa head leadership, work motivation and work culture on teacher performance. The research objects were 103 teachers spread across five MINs in Sawang District, North Aceh Regency. With quantitative methods, and processing techniques using path analysis. The results of the verification research show: a) there is a causal relationship between exogenous variables, namely principal leadership, teacher work motivation and work culture, b) there is an influence of principal leadership on teacher performance of 5.88%, the magnitude of the influence of work motivation is 5, 88%. 9.01% and the influence of work culture on teacher performance was 7.49%. c) together the leadership of the madrasa head, work motivation and work culture contribute to teacher performance, namely 22.9%.